ASSESSMENT OF THE LEVEL OF TEACHING INFORMATICS AS A SUBJECT IN TERMS OR SELECTED FACTORS - ZÁHOREC, Ján (Trends in education, 2009)
In their paper the authors present a part of their research results, they obtained within a broader research focused on possibilities to influence student's attitudes and approaches to particular subjects, mainly the less favourite ones. On the background of the obtained results they discuss here student's interest in study informatics and try to identify the reasons of student's interest or disinterest in these subjects. They try to answer the question what are currently the most powerful motivation factors for students to acquire new knowledge from these areas.
Keywords: teaching subjects; informatics; interest in study informatics; motivation factors; atractivity of teaching.